Whole-exome sequencing of consanguineous families with infertile men and women identifies homologous mutations in SPATA22 and MEIOB. Issue 10 (14th August 2021) - Wu, Yufan; Li, Yang; Murtaza, Ghulam; Zhou, Jianteng; Jiao, Yuying; Gong, Chenjia; Hu, Congyuan; Han, Qiqi; Zhang, Huan; Zhang, Yuanwei; Shi, Baolu; Ma, Hui; et al.
Abstract: STUDY QUESTION: Can whole-exome sequencing (WES) reveal pathogenic mutations in two consanguineous Pakistani families with infertile patients? SUMMARY ANSWER: A homozygous spermatogenesis associated 22 ( SPATA22 ) frameshift mutation (c.203del), which disrupts the interaction with meiosis specific with OB-fold (MEIOB), and a MEIOB splicing mutation (c.683-1G>A) that led to loss of MEIOB protein cause familial infertility. WHAT IS KNOWN ALREADY: MEIOB and SPATA22, direct binding partners and functional collaborators, form a meiosis-specific heterodimer that regulates meiotic recombination. The protein stability and the axial localization of MEIOB and SPATA22 depend on each other. Meiob and Spata22 knockout mice have the same phenotypes: mutant spermatocytes can initiate meiotic recombination but are unable to complete DSB repair, leading to crossover formation failure, meiotic prophase arrest, and sterility. STUDY DESIGN, SIZE, DURATION: We performed WES for the patients and controls in two consanguineous Pakistani families to screen for mutations. The pathogenicity of the identified mutations was assessed by in vitro assay and mutant mouse model. PARTICIPANTS/MATERIALS, SETTING, METHODS: Two consanguineous Pakistani families with four patients (three men and one woman) suffering from primary infertility were recruited. SPATA22 and MEIOB mutations were screened from the WES data, followed by functional verification in cultured cells and mice. MAIN RESULTS AND THE ROLE OF CHANCE: A homozygous SPATA22 frameshift mutation (c.203del) was identified in a patient with non-obstructive azoospermia (NOA) from a consanguineous Pakistani family and a homozygous MEIOB splicing mutation (c.683-1G>A) was identified in two patients with NOA and one infertile woman from another consanguineous Pakistani family. The SPATA22 mutation destroyed the interaction with MEIOB. The MEIOB splicing mutation induced Exon 9 skipping, which causes a 32aa deletion in the oligonucleotide-binding domain without affecting the interaction between MEIOB and SPATA22. Furthermore, analyses of the Meiob mutant mice modelling the patients' mutation revealed that the MEIOB splicing mutation leads to loss of MEIOB proteins, abolished SPATA22 recruitment on chromosome axes, and meiotic arrest due to meiotic recombination failure. Thus, our study suggests that SPATA22 and MEIOB may both be causative genes for human infertility. LIMITATIONS, REASONS FOR CAUTION: As SPATA22 and MEIOB are interdependent and essential for meiotic recombination, screening for mutations of SPATA22 and MEIOB in both infertile men and women in larger cohorts is important to further reveal the role of the SPATA22 and MEIOB heterodimer in human fertility. WIDER IMPLICATIONS OF THE FINDINGS: These findings provide direct clinical and functional evidence that mutations in SPATA22 and MEIOB can cause meiotic recombination failure, supporting a role for these mutations in human infertility and their potential use as targets for genetic diagnosis of human infertility. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the National Key Research and Developmental Program of China (2018YFC1003900, 2018YFC1003700, and 2019YFA0802600), the National Natural Science Foundation of China (31890780, 31630050, 32061143006, 82071709, and 31871514), the Strategic Priority Research Program of the Chinese Academy of Sciences (XDB19000000). The authors declare no conflicts of interest. TRIAL REGISTRATION NUMBER: N/A.